A novel method for diagnosing defective PZT-Substrate bonding in electromechanical (EM) impedance technique. (2020) - Kocherla, Amarteja; Narayanan, Arun; Duddi, Murali; Ifan, Mohammed Ayub; Kailas,; Kolluru, Subramaniam
Abstract: Surface mounted PZT (Lead Zirconate Titanate) patches are extensively used to monitor the localized and distributed damage in concrete structures in recent times. To avoid the misinterpretation of damage in the real structures the development of reliable techniques for detection and detailing of de bonding is necessary. In this study the electro mechanical impedance method is employed to detect the partial de bonding of surface mounted PZT patch. The effect of defective bonding of PZT patch on electrical impedance (EI) response spectrum investigated by combining experimental and numerical approaches. The investigation is carried out in two steps. In the first step, the experiments are carried with surface mounted PZT patches attached to the concrete substrate in perfectly bonded condition and 10% de bonded condition and the EI response spectrum is extracted in both perfectly bonded and partially de bonded conditions. The influence of finite size of substrate is eliminated from EI response spectrum to identify the influence of de bonding alone on EI response spectrum. In the second step, a numerical model is developed for a PZT patch attached to a concrete substrate using COMSOL Multiphysics. The developed numerical model is then calibrated using experimental studies, surface mounted PZT patches with different de bonding percentages are studied and their influence on the electromechanical impedance response of the bonded PZT is explored using the calibrated numerical model. The current study proposes a new effective method for diagnosing defective PZT-substrate bonding in surface mounted PZT patches attached to concrete substrate.